A Systematic review of Accuracy and Technological Advancements in X-Ray Imaging for Orthopedic Diagnostics - Bander Awad Allah Alfarsi,; Ahmed Jarwan Aljadaani,; Khalid Dakhel Alkharmani,; Abdulaziz Lwaifi Alsulami,; Mohammed Ahmed Almazrouie,; Fahad Abdulrahim Alghanmi,; Banan Hassan Abkar,; Maram Mohammed Alharbi,; Sultan Shaher Alansari,; Yousef Hamdan Attyah Alfarsi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
These systematic papers explore the precision as well as the technological growth related to x rays in terms of orthopedic diagnoses, such as the diagnosis of fracture, joint problems, and spinal injuries. Research from 2020-2024 focused on enhancements resulting from digital radiography, a three-dimensional display, and AI in diagnostics. Ongoing studies suggest that AI applications in imaging significantly enhance the detection and accuracy of fractures while revealing system limitations and the need for optimization and adaptation at the clinical level. The following review would wish to reinforce the idea of enhancement and development of adequate X-ray imaging in orthopedic diagnostics to the benefit of patients, while encouraging the use of effective imaging in the clinical environment.